MOSQUITO REPELLENCE BY SMOKE OF FRESH SHOOT SYSTEMS AND DRIED POWDER OF CASSIA OBSTUSIFOLIA, STRIGA HERMONTHICA AND HYPTIS SUAVEOLENS IN COMPARISON WITH THREE STANDARD SYNTHETIC MOSQUITO REPELLENTS IN THE GHANAIAN MARKET - Sadongo, V. W.; Awo, O.; Abagale, A. S.; Lassey, K. (UDS International Journal of Development, 2019)
The widespread use of smoke from smouldering fresh shoot systems of plants to repel mosquitoes in most African communities has frequently resulted in fire outbreaks and respiratory disorders. The current work investigated alternative ways of using plant materials devoid of burning to protect humans against mosquito borne illnesses. Mosquito repellence of samples of Striga hermonthica, Cassia obtusifolia, and Hyptis suaveolens were studied in a linear olfactometer in comparison with Sasso and Heaven black mosquito coils, and Medisoft repellent lotion. Clean air was used as control. Percentage/mean repellence by S. hermonthica were 18.7% (2.8±0.5), 50% (7.5±0.2) and 65% (9.7±0.4) using 2, 4 and 6 units of smoke respectively. That by H. suaveolens was 28%, 71% and 83% using 2, 4 and 6 units of smoke respectively. The difference in repellence by the smoke of S. hermonthica and H. suaveolens were not significantly different (P>0.05) from those of the synthetic standard coils. Dried powdered Striga hermonthica and Hyptis suaveolens leaves also repelled a mean of 6.50±0.63 and 5.42±0.70 mosquitoes respectively and the difference between them was not significant. Comparatively, powdered leaves of both plants exhibited good repellence (P>0.05) as the standard synthetic repellents. The powdered samples could be used in place of the smoke of either plants or the standard mosquito coils to manage mosquito bites through repellence. Keywords: Mosquitoes, repellents, powdered plants, compared, standard coils